2010
DOI: 10.1159/000320259
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Immunohistochemical Expression Is Enhanced in Macrophages of Symptomatic Carotid Atherosclerotic Plaques

Abstract: Background: A growing body of evidence supports a role for Toll-like receptor 4 (TLR4), a primary receptor of the innate immune system, in atherosclerosis initiation and progression. Carotid atheroma macrophages (MACs) and smooth muscle cells (SMCs) express TLR4; nevertheless, correlations with epidemiological and clinical variables and especially cerebrovascular symptomatology remain unsettled. Methods: Carotid atherosclerotic plaques were obtained by standard carotid endarterectomy on 157 patients with carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Some studies have shown that immune responses contribute to atherosclerosis [8]. In autoimmune thyroiditis with euthyroidism, vascular studies of the brachial artery showed that endothelium-mediated arterial dilation was negatively correlated with TPO-Ab, which suggests that immune responses may cause endothelial dysfunction [9].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that immune responses contribute to atherosclerosis [8]. In autoimmune thyroiditis with euthyroidism, vascular studies of the brachial artery showed that endothelium-mediated arterial dilation was negatively correlated with TPO-Ab, which suggests that immune responses may cause endothelial dysfunction [9].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it remains unclear whether oxLDL plays a role in the osteogenic responses in aortic valve cells. Interestingly, several studies indicate that oxLDL modulates TLR4 expression or signaling in macrophages, resulting in an enhanced cytokine response to TLR4 stimulation [18], [19], [20], [21], [22]. While oxLDL and bacterial products may co-exist in diseased aortic valves, the effect of oxLDL on TLR4-mediated osteogenic responses in human AVICs has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Increased endothelial expression of TLR2 at sites of disturbed blood flow exacerbates early atherogenic events (11). Increased levels of TLR4 are expressed by macrophages in murine and human lipid-rich atherosclerotic plaques (12,13). Lack of TLR4 suppresses atherosclerosis and alters plaque phenotype in mice deficient in apolipoprotein E (7).…”
mentioning
confidence: 99%